Study on plant regeneration from embryo of a group varieties of Vietnamese upland rice for transformation approach - Quyen, Cao Le; Van, Pham Thi; Hoi, Pham Xuan (Academia Journal of Biology, 2012)
Almost high land rice varieties have drought tolerant potential however they usually do not meet the demand of yield for rapid growing in the population. To utilize these potential genetics resources, it requires transferring the high yield genes into this group or introducing the potential drought tolerance genes into high yield and quality varieties. It is necessary for optimizing in-vitro culture and establishing a transgenic protocol in this group therefore we have studied on the callus forming potency and plant regeneration capacity of 46 Vietnamese high land rice varieties. Almost of them (44/46 rice varieties) have callus forming potency and there are 22 rice varieties which have callus formation rate more than 50%, especially four varieties have callus formation rate approximately from 70% to 80%. The MS medium supplement with a range of 1.5-2 mg/l 2,4D seems to be optimal for callus forming. All 25 callus forming rice varieties showed plant regeneration capacity and out of which, six rice varieties have regeneration score above 55%. The MS medium supplement with 2 mg/l BAP, 0.5 mg/l kinetin, and 0.1 mg/l casein seem to be optimal for plant regeneration. The ANOVAs analyses show that the callus forming potency and plant regeneration capacity of this group are influenced by mediums and genetic resources. However, the medium factors effect in the callus forming potency stronger than genetic resources while plant regeneration capacity depends on their genetics more than media. STUDY ON PLANT REGENERATION FROM EMBRYO OF A GROUP VARIETIES OF VIETNAMESE UPLAND RICE FOR TRANSFORMATION APPROACH